Technique for in situ measurement of calcium in intracellular inositol 1,4,5-trisphosphate-sensitive stores using the fluorescent indicator mag-fura-2. - Hofer, A M (1993)
Stimulation of cells with calcium-mobilizing agonists frequently results in inositol 1,4,5-trisphosphate (InsP3)-mediated discharge of Ca from an internal store. We report here a technique for directly monitoring Ca within this and other stores in gastric epithelial cells. This technique takes advantage of the propensity of the acetoxymethyl ester derivative of the fluorescent dye mag-fura-2 (which is sensitive to Ca concentrations above 5 microM) to accumulate in subcellular compartments where it can report changes in the free Ca concentration. Intact dye-loaded cells responded to cholinergic stimulation with a decrease in the 350 nm/385 nm excitation ratio, as measured in individual cells with a digital imaging microscope, consistent with reduced Ca concentration in one or more cellular compartments. When cells were permeabilized with digitonin and incubated in an "intracellular buffer," the cytoplasmic dye was released, leaving the mag-fura-2 in the internal store. InsP3 caused the ratio from the trapped indicator to decrease (i.e., Ca was released) in a dose-dependent manner, and this effect was blocked by the InsP3 receptor antagonist heparin. Ca sequestration into the internal store was ATP-dependent, and reuptake into the InsP3-sensitive pool was blocked by thapsigargin, a specific inhibitor of the Ca-ATPase of the internal store. We used this technique to investigate the role of Cl on the release and reloading of the InsP3-sensitive internal store and found that Ca uptake was reduced in Cl-free solutions, suggesting an important function for Cl in the refilling of this pool.